Woman Without Her Man Is Nothing. Issue 1 (April 2020) - Gillespie, William
Abstract : There are various keys to William Gillespie's piece, which is extracted from his forthcoming book Your Guide to Getting a Divorce in Illinois (Spineless Books, 2020), and structured through lexias that blend the narration of cleaving and separation across a relationship with aphoristic questioning and reflection. One sentence, however, effectively primes the text. 'Birth pluralizes, death singulates.' It finds refractions across the piece, working off themes involving loneliness and otherness, and around patterns that extend from individuality to 'the universe – literally everything'. The text thereby explores the (im/inter)personality of 'being singular plural', delivering a striking performance of tonally complex terseness.